Comparison of reproductive performance, live weight, survivability, and fleece characteristics of indoor-raised Central Anatolian Merino and Malya sheep - Sedat Behrem; Selçuk Seçkin Tuncer; Hasan Hüseyin Şenyüz (Revista Brasileira de Zootecnia, 2022)
ABSTRACT This study was conducted to compare Central Anatolian Merino (CAM) and Malya sheep under intensive conditions in terms of reproductive traits, birth and weaning weights, fattening performance, and some fleece characteristics. In this study, 840 CAM and 194 Malya ewes were used for the comparison of reproductive performance, whereas 740 and 211 lambs were used to compare growth traits between the two breeds. Additionally, the fattening performance of 61 CAM and 68 Malya lambs were compared. Finally, for the comparison of wool quality traits, 94 CAM and 90 Malya lambs were used. The lambs were kept together with the sheep that gave birth to them for 10 days. After this period, lambs were given lamb starter feed, alfalfa hay, and vetch hay in addition to milk. When lambs reached 40 days old, they were taken to the pasture with the sheep. In this period, pasture grass, growing lamb concentrate feed, alfalfa hay, and vetch hay were given in addition to milk. Lambs were weaned when they reached an average age of 90 days, and their live weights were determined. A determined number of lambs was selected from weaned male lambs. For these animals, in the fattening period, barley, alfalfa hay, vetch hay, meadow hay, and lentil straw were provided ad libitum in addition to 400 g/day/head of fattening feed. This study indicated that birth rate was better for CAM sheep than for Malya sheep. However, Malya lambs may have more advantages than CAM lambs in terms of survival and fattening performance. Although birth weight was higher for Malya sheep than for CAM sheep, the opposite result was observed for the weaning weight. The beginning weights of fattened male lambs were higher for CAM lambs than for Malya lambs, but the ending weights of both fattened groups were similar.